Working for Small Change: Investigating the Livelihoods of Ride-hailing Drivers in Cape Town, South Africa - Stein, Malte (Department of Environmental and Geographical Science, 2022)
Since its introduction in 2009, ride-hailing has been at the centre of many critical discussions concerning the disruption of the (public) transportation sector, labour issues and tax matters. Missing voices in this discourse have notably been the employees of ride-hailing companies, specifically in the Global South. Setting out to inquire about the living and working conditions of ride-hailing drivers, this study employed a qualitative research framework and ethnographic methods in a case study of Uber drivers in Cape Town, South Africa. Semi-structured and in depth interviews were used as leading method to find out more about the drivers' hopes, troubles, aspirations and coping mechanisms. Particularly in the Global South, the growing informalisation and commodification of labour pose a threat to workers. Drivers in need of income are subject to unstable short-term employment that is low pay, does not offer social security, exhibits highly uneven employment relationships, includes large financial risks and predominantly serves customer and corporate interests. Yet, countering fatalistic narratives that frame drivers as helpless and exposed, this thesis offers accounts of creative rule-bending, mitigation strategies and community organisation used to mitigate precarity. I argue that ride hailing work is located at least partially in a grey zone as the everyday struggle for opportunity forces workers to search for alternative spaces on the fringes between the formal and informal and the legal and illegal. In a comparable manner, ride-hailing companies use legal grey zones and loopholes to advance their business and become the benefactors of the precarious hustle of thousands of mostly migrant drivers in South Africa. This study adds in-depth and original ethnographic research and critical theorisation to the literature on ride-hailing and the living and working conditions of marginalised workers. It illustrates the urgent need to further inquire about the proliferating commodification and informalisation that ride-hailing and the gig economy entails in the Global South.